Effects of calcination conditions on phase formation and particle size of indium niobate nanopowders synthesized by the solid-state reaction - S. Wongsaenmai (2018)
A wolframite-type phase of indium niobate, InNbO4, has been synthesized by a solid-state reaction via a rapid vibro-milling technique. The formation of the InNbO4phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM and EDX techniques. It has been found that single-phase InNbO4powders have been obtained successfully at the calcination condition of 950 °C for 2 h with heating/cooling rates of 30 °C/min. Higher temperatures and longer dwell times clearly favoured particle growth and the formation of large and hard agglomerates. © 2006 Elsevier B.V. All rights reserved.